Developing a tool for measuring postpartum women's experiences of respectful maternity care at a tertiary hospital in Kumasi, Ghana - Veronica Millicent Dzomeku; Adwoa Bemah Boamah Mensah; Kweku Emmanuel Nakua; Pascal Agbadi; Jody R. Lori; Peter Donkor (Heliyon, 2020)
The authors of this paper are involved in a 5 years respectful maternity care (RMC) project at a tertiary healthcare facility in Kumasi, Ghana that seeks to change the culture of disrespect and abuse in maternity care practice, with a sub-objective of determining its impact on how midwives provide quality maternity care services in this healthcare facility. To achieve this objective, respectful maternity care must be conceptualized and measured. Our literature search revealed that a Ghanaian version tool that measures women's experiences of respectful maternity care is non-existent. Thus, this study aims to construct a scale that measures childbearing women's experiences of respectful maternity care during childbirth and the immediate postpartum period in the study setting. We surveyed 263 postpartum women with a draft scale we have developed. This scale had 42 questions that sought to measure postpartum women's experiences of respectful maternity care in a tertiary health facility in Kumasi. The scale development went through processes of exploratory factor analyses (EFA) and inter-item reliability tests. The EFA was done using SPSS-21. Through series of EFA, we have created a 23 items RMC scale (23i-RMC) with three main factors labelled as follows: Verbal abuse-free, Discriminatory-free and Dignified care (VADDC), Physical and Psychological Abuse-free care (PPAC), and Compassionate Care (CC). The Cronbach's Alpha of the 23i-RMC is 0.945 and those of the individual domains greater than the 0.70 minimum threshold, suggesting that there is greater reliability among the items in the scale and the subscales. This 23i-RMC scale is useful for assessing postpartum women's experiences of RMC in the study setting. We recommend the use and validation of the newly developed respectful maternity care scale in other healthcare facilities in Ghana.